Gastrointestinal microplastic abundance in relation to fish feeding guilds in Balikpapan Bay, East Kalimantan, Indonesia - BITTARAE F. H. SJAMSIR; TRI DEWI K. PRIBADI; GHITARINA GHITARINA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sjamsir BFH, Pribadi TDK, Ghitarina. 2026. Gastrointestinal microplastic abundance in relation to fish feeding guilds in Balikpapan Bay, East Kalimantan, Indonesia. Biodiversitas 27 (4): d270420. https://doi.org/10.13057/biodiv/d270420. Microplastic pollution in marine ecosystems has emerged as a major environmental concern, particularly in regions with intense human activity. This study examined the relationship between feeding guild and gastrointestinal microplastic abundance in fish from Balikpapan Bay, Indonesia. A total of 162 fish representing 25 species, 21 families, and 11 orders were collected, of which 133 individuals from all 25 species were analyzed for gastrointestinal microplastic contamination. Microplastics were extracted using chemical digestion, identified under a stereomicroscope, and polymer composition was confirmed using pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). In total, 1,378 microplastic particles were detected, with an average abundance of 10.35±3.80 particles per fish. Fibers dominated the particles (57.4%), followed by fragments (35.0%), films (4.5%), beads (2.2%), and foam (0.9%). Polymer analysis identified nylon as the dominant polymer type, suggesting fishing gear as a probable source. Microplastic abundance differed significantly among feeding guilds (Kruskal-Wallis test, p<0.05), with herbivorous species exhibiting the highest abundances, while no significant difference was observed between demersal and pelagic fish. These findings provide baseline data on microplastic contamination in fish from an intensively used tropical coastal system and suggest exposure may vary with feeding guild, with herbivorous species potentially more vulnerable to contamination associated with high-volume grazing on benthic substrates, where microplastics accumulate and adhere to biofilms.